PEMANFAATAN CERITA RAKYAT SEBAGAI MEDIA BIBLIOTERAPI BAGI ANAK - Siti Anafiah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
Folklore is one type of child literature that has great benefits for its readers. One of the benefits of folklore is as a media biblioterapi for children. Bibliotherapy is a reading therapy, in which a person with problems is asked to read self-help books and motivate them to speed healing. Folklore can help to overcome problems faced by children. Folklore especially the fairy tale that has been favored by children not only provide basic education about the absorption of moral messages and characters, but more than that through fairy tales can be a means of non-formal education that can be utilized by teachers and parents in restoring trauma and meet thirsty children with other special needs.